Społeczność lokalna, zbiorowość terytorialna a instyncjonalizacja ideologii lokalizmu/regionalizmu = Local community, territorial collectivity and the process of ideology institutionalization of localism/regionalism - Radziewicz-Winnicki, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents a new theoretical approach - against the background of all the papers included in this volume - to the development of local and regional systems. Contemporary ideas existing in the literature of social sciences should be, in the author`s opinion, collected and considered in the modern category of localism which becomes an important element of the organization of citizen`s life during the social change in post-communist Poland. The author tries to formulate his own position and the point of view in that approach. This concept is also compared with the traditional conceptualization of the vision of the development and activity in local civic communities.
Keywords: społeczność lokalna; zbiorowość terytorialna; regionalizm; Uniwersytet Zielonogórski; Uniwersytet Zielonogórski - Wydział Pedagogiki, Socjologii i Nauk o Zdrowiu